The quality of nursing in intensive care: a development of a rating scale - La Sala, Rachele; Galfrè, Elena; Bertani, Laura; Mingolla, Valentina; Murelli, Silvia; Messina, Giuseppina (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The evaluation of nursing care is a topic of great interest and especially crucial in intensive care contexts. However, inside the Italian scientific scenario it is still difficult to measure NSO, or Nursing Sensitive Outcomes, due to the lack of indicators or scales shared by the nursing community. The aim of the present study was therefore to develop a Quality Nursing Care Scale for the Intensive Care (ICU-I-QNCS). Method: From the literature review of the Intensive Care Unit (ICU) quality standards, they were generated 63 items. Then 43 experts assessed them through the Content Validity Index (CVI). Items with a CVI score <0.90 were removed from the scale. Results: All the 63 items have achieved an average score CVI equal or greater than 0.90. 5 item reached an optimal average CVI score (=1); 23 showed an average CVI score between 0.90-0.94 and last 35 were between 0.95-0.99. Conclusions: The ICU-I-QNCS has obtained an acceptable CVI level and it reflects the underlying theoretical model of Doran (2002).